2021
DOI: 10.1371/journal.pone.0259671
|View full text |Cite
|
Sign up to set email alerts
|

Combined impact of TiO2 nanoparticles and antibiotics on the activity and bacterial community of partial nitrification system

Abstract: The effects of TiO2 nanoparticles (nano-TiO2) together with antibiotics leaking into wastewater treatment plants (WWTPs), especially the partial nitrification (PN) process remain unclear. To evaluate the combined impact and mechanisms of nano-TiO2 and antibiotics on PN systems, batch experiments were carried out with six bench-scale sequencing batch reactors. Nano-TiO2 at a low level had minimal effects on the PN system. In combination with tetracycline and erythromycin, the acute impact of antibiotics was enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…TiO 2 NPs are recognized as highly versatile nanoparticles and are used in coating reagents, cosmetics, medicine, and numerous other industries (Fan et al, 2023; Qiu et al, 2021; Sun et al, 2017). TiO 2 NPs mainly exhibit three crystal forms, namely, anatase, rutile, and brookite.…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 NPs are recognized as highly versatile nanoparticles and are used in coating reagents, cosmetics, medicine, and numerous other industries (Fan et al, 2023; Qiu et al, 2021; Sun et al, 2017). TiO 2 NPs mainly exhibit three crystal forms, namely, anatase, rutile, and brookite.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of TiO 2 NPs with antibiotics has been revealed to be advantageous in improving antibacterial activity. Xu et al [ 78 ] have demonstrated that TiO 2 NPs at a low level had minimal effects on a wastewater treatment plant, whereas, in combination with tetracycline and erythromycin, the impact of antibiotics was enhanced. This enhanced antibiotic toxicity effect was due to the increasing cell permeability induced by nano-titania.…”
Section: Tio 2 Np Antibacterial Activitymentioning
confidence: 99%
“…The effects on the cell walls, the cell membranes, the DNA and other bacterial processes were described. Inactivation and killing of bacteria by TiO 2 under radiation 18 and by combination with antibiotics 19 were described. TiO 2 particles mixed with other species such as Si have been recently described as antibacterial photocatalysts.…”
Section: Introductionmentioning
confidence: 99%